Pendampingan dan Akses Modal sebagai Strategi Access Reform dari Tanah Pelepasan Kawasan Hutan di Kabupaten Barito Kuala - Saheriyanto; Suhaimi, Ahmad (Jurnal Pertanahan, 2021)
ABSTRACT Barito Kuala Regency has excellent agricultural potential that supports the success of agrarian reform in South Kalimantan Province. Access reform presents in the integration of land asset management from the release of forest areas and structuring access as a support for the empowerment of pineapple cultivation and processing activities located in Mekarsari District aims to increase the income of rural communities. This type of qualitative descriptive research with a case study approach on the implementation of access reform at the Land Redistribution of Agrarian Reform Objects for the release of forest areas in Barito Kuala Regency. Collecting data by conducting interviews and document studies. Determination of respondents was carried out by purposive sampling of respondents and triangulation techniques were carried out to check the validity of the data. In this study, the implementation of the Agrarian Access Reform Policy includes social mapping, facilitation and collaboration with related parties, counseling, development of empowerment models and empowerment assistance. Meanwhile, based on the SWOT analysis, strategies that should be applied for the sustainability of access reform are building synergistic cooperation with parties related to agrarian reform activities, forming working groups for empowering community land rights, significantly encouraging community empowerment/access reform activities through the provision of various types of facilitation (supply seeds, fertilizers and pest control from the Department of Agriculture), assisting marketing by introducing major regional events and online marketing, bridging access to business capital loans based on subject data by name by address of recipients of land redistribution, facilitating the borrowing of heavy equipment for land processing, socializing the importance of access to reform for community economic development, recruiting field staff to provide business assistance in the community. Keywords: Acces Reform, Release of Forest Area ABSTRAK Kabupaten Barito Kuala memiliki potensi pertanian unggulan yang mendukung keberhasilan reforma agraria di Provinsi Kalimantan Selatan. Salah satu bentuk reforma agraria, yaitu integrasi penataan aset dari hasil pelepasan kawasan hutan dan penataan akses berupa dukungan kegiatan pemberdayaan budi daya dan pengolahan buah nanas yang terletak di Kecamatan Mekarsari dengan tujuan untuk meningkatkan pendapatan masyarakat desa. Jenis penelitian ini adalah kualitatif deskriptif dengan pendekatan studi kasus pada pelaksanaan access reform di lokasi Redistribusi Tanah Objek Reforma Agraria (TORA) pelepasan kawasan hutan di Kabupaten Barito Kuala. Pengumpulan data dengan melakukan wawancara dan studi dokumen. Penentuan responden dilakukan secara purposive sampling terhadap responden dan dilakukan teknik triangulasi pemeriksaan keabsahan data. Berdasarkan penelitian ini, implementasi Kebijakan Reforma Agraria Access Reform meliputi pemetaan sosial, fasilitasi dan kerjasama dengan pihak terkait, penyuluhan, penyusunan model pemberdayaan dan pendampingan pemberdayaan. Sedangkan berdasarkan analisis SWOT, strategi yang dapat diterapkan demi keberlanjutan access reform yaitu membangun kerjasama sinergis dengan para pihak terkait kegiatan reforma agraria, membentuk kelompok kerja pemberdayaan hak atas tanah masyarakat, mendorong secara signifikan kegiatan pemberdayaan masyarakat/access reform melalui pemberian aneka jenis fasilitasi (bantuan bibit, pupuk dan pembasmi hama dari Dinas Pertanian), membantu pemasaran dengan mengenalkan saat acara-acara besar di daerah dan pemasaran online, menjembatani akses peminjaman modal usaha berdasarkan data subjek by name by addressÂ  penerima redistribusi tanah, memfasilitasi peminjaman alat berat untuk pengolahan lahan, menyosialisasikan pentingnya akses reform terhadap perkembangan ekonomi masyarakat, merekrut tenaga field staff untuk melakukan pendampingan usaha di masyarakat. Kata Kunci: Acces Reform, Pelepasan Kawasan Hutan